The Implementation of Semitic Rhetorical Analysis on QS. Al-Ahqaf - Yudantia, Ditta Maya; Asnawi, Aqdi Rofiq; Hadi, Abd; Rohman, Abdur (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This article will discuss the implementation of Semitic Rhetorical Analysis to one of the surah in the Qur'an, namely Surah Al-Ahqaf. In the past scholars have also applied SRA to surah in the Qur'an to show unity and wholeness to the suras, this is done to prove Cuypers' words which say that although SRA is a rhetorical theory used to study the Bible, SRA is also able to prove the integrity of suras in the Qur'an. He stated that after he succeeded in applying the surah Al-Ma'idah and the last 30 suras in the Qur'an, he also claimed that his success in studying these surahs adequately represented that the entire surah in the Qur'an is composed by the principles of the SRA and forms a complete unity of surahs. Nevertheless, this claim must be proven by applying SRA to all surahs in the Qur'an, one of which is to surah Al-Ahqaf whose integrity is disputed by an orientalist named Richard Bell. He argues that the mention of jinn in verse 29 lacks the unity of discussion in surah Al-Ahqaf, it also makes the last few verses seem isolated from the discussion listed at the beginning of the surah. Therefore, the author tries to refute this statement by applying the SRA theory. In this case, a library research study is carried out by referring to books, paper articles related to the discussion. Then analyzed with analytical descriptive methods so that conclusions can be found. This study proves that the integrity of surah Al-Ahqaf can be seen from its arrangement in accordance with the principles of SRA, the arrangement also gives birth to interpretations that are in accordance with the ulama' tafsir.